Ensuring the Future of Métis Well-Being through Heart-Work and Digital Means - Poitras Pratt, Yvonne; Grant, Billie-Jo (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
As Métis educators working in Alberta, we have long advocated for the meaningful inclusion of Métis perspectives and relational ways in educational spaces. We take up this work of advocacy and critical scholarship to honour our ancestors and ensure that the next generations of Métis are firmly rooted in their identity and empowered with confidence to assert their presence. Despite our efforts and those of many dedicated others who see the need for equity and inclusion in Indigenous education, our attempts to interrupt dominant settler-colonial logics have only been marginally successful. This article explores how a lack of knowingness around the Métis, flawed notions of racial purity, and assumptions of full assimilation of the Métis have resulted in ongoing injustices against the Métis. We share how we have worked to rectify these inequities through digital means alongside the prioritization of traditional Métis values that include respect, relational ways, and reciprocity.